Answer:
x(t)=[tex]2-2e^{-t}-2te^{-t}[/tex]
Step-by-step explanation:
The function x(s) = (2)/(s(s+1)^2) can be expressed as partial fractions:
X(s)=[tex]\frac{2}{s(s+1)^2}=\frac{A}{s}+\frac{B}{s+1}+\frac{C}{(s+1)^2}[/tex]
2=A·(s+1)²+B·s·(s+1)+C·s
2=A·(s²+2s+1)+B·(s²+s)+C·s
2=A·s²+2sA+A+B·s²+Bs+C·s
2=s²(A+B)+s(2A+B+C)+A
So we can find the values of A, B and C by solving these equations:
A+B=0 ⇒ 2+B=0 ⇒ B= -2
2A+B+C=0 ⇒ 2·2+(-2)+C=0 ⇒ C= -2
A=2
So X(s) is expressed as:
X(s)=[tex]\frac{2}{s}+\frac{-2}{s+1}+\frac{-2}{(s+1)^2}[/tex]
Using the inverse laplace transform tables we obtain x(t):
ℒ⁻¹{X(s)}=ℒ⁻¹{[tex]\frac{2}{s}+\frac{-2}{s+1}+\frac{-2}{(s+1)^2}[/tex]}
ℒ⁻¹{X(s)}=ℒ⁻¹{[tex]\frac{2}{s}[/tex]}+ℒ⁻¹{[tex]\frac{-2}{s+1}[/tex]}+ℒ⁻¹{[tex]\frac{-2}{(s+1)^2}[/tex]}
x(t)=[tex]2-2e^{-t}-2te^{-t}[/tex]